Effect of cyclo-oxygenase inhibitor use during checkpoint blockade immunotherapy in patients with metastatic melanoma and non-small cell lung cancer. Issue 2 (5th October 2020) - Wang, Shang-Jui; Khullar, Karishma; Kim, Sinae; Yegya-Raman, Nikhil; Malhotra, Jyoti; Groisberg, Roman; Crayton, Samuel H; Silk, Ann W; Nosher, John L; Gentile, Michael A; Mehnert, Janice M; Jabbour, Salma K
Abstract : Background: Immune checkpoint inhibitors (ICIs) improve survival outcomes in metastatic melanoma and non-small cell lung cancer (NSCLC). Preclinical evidence suggests that overexpression of cyclo-oxygenase-2 (COX2) in tumors facilitates immune evasion through prostaglandin E2 production and that COX inhibition synergizes with ICIs to promote antitumor T-cell activation. This study investigates whether concurrent COX inhibitor (COXi) use during ICI treatment compared with ICI alone is associated with improved time-to-progression (TTP), objective response rate (ORR) and overall survival (OS) in patients with metastatic melanoma and NSCLC. Methods: We retrospectively reviewed 90 metastatic melanoma and 37 metastatic NSCLC patients, treated with ICI between 2011 and 2019. Differences in TTP and OS by ICI+COXi versus ICI alone were compared using Kaplan-Meier and Cox regression. Interaction between ICI+COXi versus ICI alone and pretreatment neutrophil–lymphocyte ratio (NLR) was examined. Independent radiology review per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1 was performed. Results: For patients with melanoma, median TTP was significantly prolonged in ICI+COXi versus ICI alone (245 vs 100.5 days, p=0.002). On multivariate analysis, ICI+COXi associated with increased TTP (HR 0.36, 95% CI 0.2 to 0.66, p=0.001), adjusted for age, pretreatment NLR, and gender. For NSCLC patients, ICI+COXi also associated with increased TTP compared with ICI alone on multivariate analysis (HR 0.45; 95% CI 0.21 to 0.97; p=0.042) adjusted for age. ORR at 6 months was significantly higher in patients who received ICI+COXi compared with ICI alone in both melanoma (58.6% vs 19.2%, p=0.0005) and NSCLC (73.7% vs 33.3%, p=0.036) cohorts. In the melanoma cohort, high pretreatment NLR (>5) associated with decreased TTP (HR 3.21, 95% CI 1.64 to 6.3; p=0.0007); however, ICI+COXi significantly associated with increased TTP in high NLR (>5) patients (HR 0.08, 95% CI 0.03 to 0.25), but not in low NLR (≤5) patients (HR 0.65, 95% CI 0.32 to 1.32). Similar outcomes were found in an adjusted melanoma cohort after RECIST review. Conclusions: Our study suggests that COXi use concurrently with ICI significantly associated with longer TTP and improved ORR at 6 months in patients with metastatic melanoma and NSCLC compared with ICI alone. Furthermore, COXi use appears to reverse the negative prognostic effect of a high NLR by prolonging TTP in patients with melanoma.